Tarzan. - Collins, Phil; Zainal Abidin; Sony Music Entertainment (Malaysia). (Ampang, Selangor : Sony Music Entertainment, 1998)
Contains four songs from Tarzan soundtrack sung by Phil Collins in English and Zainal Abidin in Malay.
CD 1 : You'll Be In My Heart / Phil Collins (4:18) -- Kau Di Hatiku / Zainal Abidin (4:16) -- Two Worlds / Phil Collins (2:43) -- Dua Dunia / Zainal Abidin (2:44).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Film soundtracks; Motion picture music; Popular music